Design and Implementation of Smart Home Gateway Based on 433MHz Radio-Frequency Communication - Lei, Du; Wenbin, Cheng (Recent Advances in Electrical & Electronic Engineering, 2018)
Background: In view of the lack of centralized control of traditional home appliances, this paper implements an intelligent gateway based on the Linux embedded operating system as the software platform and the ARM9 processor S3C2440 as the hardware development platform to solve this problem. Methods: The intelligent gateway is equipped with Wi-Fi, CC1101, Ethernet card and other functional modules, and based on the 433MHz radio-frequency protocol stack and the Linux operating system kernel. We establish the platform of the remote control through the cloud server, so the users can log on the client to achieve smart home remote monitoring. Result: This paper introduces the hardware and software development process of intelligent gateway, which involves the realization of the 433MHz radio-frequency protocol stack, the software design of the 433MHz radio-frequency module, and the design and implementation of the smart home client and so on. Conclusion: The test results show that the intelligent gateway has the characteristics of low-cost, low-power consumption, high reliability.
Keywords: CC1101